Maximising high solid loading enzymatic saccharification yield from acid-catalysed hydrothermally-pretreated brewers spent grain - Wilkinson, Stuart; Smart, Katherine A.; James, Sue; Cook, David J. (Green Wave Publishing of Canada, 2016)
Enzyme saccharification of pretreated brewers spent grains (BSG) was investigated, aiming at maximising glucose production. Factors investigated were; variation of the solids loadings at different cellulolytic enzyme doses, reaction time, higher energy mixing methods, supplementation of the cellulolytic enzymes with additional enzymes (and cofactors) and use of fed-batch methods. Improved slurry agitation through aerated high-torque mixing offered small but significant enhancements in glucose yields (to 53 ± 2.9 g/L and 45% of theoretical yield) compared to only 41 ± 4.0 g/L and 39% of theoretical yield for standard shaking methods (at 15% w/v solids loading). Supplementation of the cellulolytic enzymes with additional enzymes (acetyl xylan esterases, ferulic acid esterases and α-L- arabinofuranosidases) also boosted achieved glucose yields to 58 – 69 ± 0.8 - 6.2 g/L which equated to 52 - 58% of theoretical yield. Fed-batch methods also enhanced glucose yields (to 58 ± 2.2 g/L and 35% of theoretical yield at 25% w/v solids loading) compared to non-fed-batch methods. From these investigations a novel enzymatic saccharification method was developed (using enhanced mixing, a fed-batch approach and additional carbohydrate degrading enzymes) which further increased glucose yields to 78 ± 4.1 g/L and 43% of theoretical yield when operating at high solids loading (25% w/v).